Human papillomavirus E1 proteins inhibit RIG-I/MDA5-MAVS, TLR3-TRIF, cGAS-STING, and JAK-STAT signaling pathways to evade innate antiviral immunity - Li, Jin-Xin; Zhang, Jing; Li, Cheng-Hao; Li, Yun-Fang; Chen, Hui-Min; Li, Tao; Zhang, Qing; Kong, Bei-Hua; Wang, Pei-Hui (Frontiers in Immunology, 2025)
Human papillomavirus (HPV) is a major etiological agent of both malignant and benign lesions, with high-risk types, such as HPV16 and HPV18, being strongly linked to cervical cancer, while low-risk types like HPV11 are associated with benign conditions. While viral proteins such as E6 and E7 are well-established regulators of immune evasion, the role of E1 in modulating the host antiviral responses remains insufficiently characterized. This study investigates the immunomodulatory functions of HPV16 and HPV11 E1 in suppressing innate antiviral immune signaling pathways. Through a combination of RT-qPCR and luciferase reporter assays, we demonstrate that E1 suppresses the production of interferons and interferon-stimulated genes triggered by viral infections and the activation of RIG-I/MDA5-MAVS, TLR3-TRIF, cGAS-STING, and JAK-STAT pathways. Co-immunoprecipitation assays reveal that E1 interacts directly with key signaling molecules within these pathways. E1 also impairs TBK1 and IRF3 phosphorylation and obstructs the nuclear translocation of IRF3, thereby broadly suppressing IFN responses. Additionally, E1 disrupts the JAK-STAT pathway by binding STAT1, which prevents the assembly and nuclear localization of the ISGF3 complex containing STAT1, STAT2, and IRF9, thereby further diminishing antiviral response. These findings establish E1 as a pivotal regulator of immune evasion and suggest its potential as a novel therapeutic target to enhance antiviral immunity in HPV-associated diseases.